Validation and cross-cultural adaptation of the questionnaire ThyPRO in thyroid patients in Serbia - Bukvić, Branka Radojle; Živaljević, Vadan; Šipetić, Sandra; Diklić, Aleksandar; Taušanović, Katarina; Paunović, Ivan (Vojnosanitetski pregled, 2015)
Backgraund/Aim. The Thyroid Specific Patient Reported Outcome Measure (ThyPRO) questionnaire is self-administered and intended to measure quality of life of thyroid patients. The aim of this study was to investigate the validity and reliability of the translated new, ThyPRO questionnaire in Serbian patients with thyroid disease. Methods. The translation process followed an internationally accepted methodology. The questionnaire was validated in 100 consecutive thyroid patients hospitalized in a tertiary level hospital, between April and August 2012. Internal reliabilities of ThyPRO scales were assesessed using Cronbach’s α coefficient. Association between age, gender, education, marital and employment status, place of living, diagnosis, current treatment, hormonal status and patient quality of life were determined using Pearson’s (r) and Spearman’s (q) correlation coefficients. Results. Internal consistency and reliability for ThyPRO scales were satisfactory. Cronbach’s α coefficients of 13 multi-item scales of the ThyPRO were > 0.83 (range 0.83–0.95). The scores, obtained by this questionnaire, correlated significantly with patients gender, employment status, diagnosis, current treatment and place of living. A highly significant inverse relationship was found between scores and hormonal status as well as between scores and disease duration. Patients’ age, marital status and thyroid-stimulating hormone level did not influence any scale score. Conclusion. The ThyPRO may be useful in measuring health-related quality of life in patients with thyroid disease in Serbia.
Keywords: quality of life; questionnaires; thyroid diseases; hypothyroidism; hyperthyroidism